If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -20 = 5x + -20 Reorder the terms: -20 + 6x = 5x + -20 Reorder the terms: -20 + 6x = -20 + 5x Add '20' to each side of the equation. -20 + 20 + 6x = -20 + 20 + 5x Combine like terms: -20 + 20 = 0 0 + 6x = -20 + 20 + 5x 6x = -20 + 20 + 5x Combine like terms: -20 + 20 = 0 6x = 0 + 5x 6x = 5x Solving 6x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 6x + -5x = 5x + -5x Combine like terms: 6x + -5x = 1x 1x = 5x + -5x Combine like terms: 5x + -5x = 0 1x = 0 Divide each side by '1'. x = 0 Simplifying x = 0
| 4y/5=9/3 | | 532/x+3=79 | | 4c-(5)+14c=67 | | (X-2)(2x^2-3x-2)= | | 5.4x+3.2=14 | | -5x-14=3x+10 | | 1.5x+3.6=15.6 | | 16/17*-3/4 | | 8x-5+5x-10=180 | | 2(x-9)-4=x-8(3) | | 3/5t-1/10t=t-5 | | 3/7=x-4/7 | | 8x-3(x+2)=7x-2x+9 | | -5r-(2r+8)=16 | | m/2+24/8=100 | | w=100-2(10+2w) | | 1-2(-2)=3(-5) | | 12x+24=2(x-8) | | 678/x*4+5=457 | | 5x+0.5=.4x | | 4x+(14x-6)=84 | | 8ab-7b+12ab-b= | | 2x-2/6=2x+2/10 | | 2x-10=-6x-58 | | 5(6x-4)=6x+4 | | (X+1)(x^2+1)= | | x-9/2-4=x-8/3 | | 13.13=2g+3.61 | | -7x-9x= | | 6-3+2= | | 9/16x=2 | | 4/12=-12/n |